Determination of Stilling Basin Invert Elevation and Its Effect on Controlling Hydraulic Jumps - Farzin F. Salmasi; John Abraham (Techniques and Innovation in Engineering Research Vol. 2, 2022)
Potential energy is transformed into kinetic energy when water is released over chutes or spillways. This energy needs to be released in order to avoid the danger of serious erosion of the downstream riverbed and the weakening of the foundation, both of which could lead to failure of the spillway and dam. For this purpose, energy dissipators must be used to reduce the kinetic of the water flow by converting the energy into highly turbulent flow and finally into thermal energy. Several techniques, such as stilling basins, can be used to release excess energy. For instance, the construction of a hydraulic leap in the stilling basin will do so. In this work, a simple method is presented for calculating the stilling basin invert elevation in relation to the elevation of the upstream water, the design discharge, and the elevation of the downstream water and tail water. To illustrate the capabilities of the design procedure, very few examples are given.